Papua New Guinea Economic Update, July 2020 : In the Time of COVID-19 - From Relief to Recovery - World Bank Group (World Bank, Washington, DC, 2020)
Papua New Guinea’s economy has been hit hard by the COVID-19 crisis due to weaker demand and less favorable terms of trade. Pandemic-related global and national movement restrictions have weakened external and domestic demand and affected commodity prices, which will lead to an economic contraction, wider financing gaps in the external and fiscal accounts, and higher unemployment and poverty than previously anticipated in 2020. The authorities reacted swiftly to the emerging external shock by developing a package of emergency health and economic relief measures. While the focus of the authorities is currently on crisis mitigation measures, they should also look beyond the current year at a more robust and resilient recovery over the medium term. In addition to the economic analysis, the report contains additional sections dedicated to physical infrastructure development in PNG. The infrastructure section suggests that the provision of more equitable access to quality infrastructure will be crucial once the country moves to the recovery and resilience phase of COVID-19 response. While improving the quality of infrastructure in PNG faces serious constraints, the country’s abundance of natural resources is a potential source for financing the work and government’s stated vision and strategy can provide necessary policy guidance.